2018
DOI: 10.1302/2058-5241.3.160089
|View full text |Cite
|
Sign up to set email alerts
|

Locked posterior dislocation of the shoulder

Abstract: Locked posterior dislocation of the shoulder is very rare. Seizures and trauma are the most common causes of this injury.There is no current benchmark treatment strategy for these rare cases.This study has shown that reconstruction of the shoulder joint in an anatomical way in acute and chronic cases up to 16 weeks provides good results.The purpose of this study is to evaluate the results of different treatment procedures with outcomes and to compare the results of the same procedures in acute and chronic case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 67 publications
4
43
0
Order By: Relevance
“…The clinical treatment depends on a number of anatomical and functional factors that must be evaluated in each patient. The treatment can be either nonoperative or surgical: The nonoperative approach is adopted when the dislocation is stable after a reduction maneuver and when there are no significant bone deficits; after the maneuver, the shoulder is immobilized for a limited period of time [ 8 , 9 ]. On the other hand, surgical treatments are preferred when the trauma has caused joint instability or lesions of bone or soft tissues that require surgical stabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical treatment depends on a number of anatomical and functional factors that must be evaluated in each patient. The treatment can be either nonoperative or surgical: The nonoperative approach is adopted when the dislocation is stable after a reduction maneuver and when there are no significant bone deficits; after the maneuver, the shoulder is immobilized for a limited period of time [ 8 , 9 ]. On the other hand, surgical treatments are preferred when the trauma has caused joint instability or lesions of bone or soft tissues that require surgical stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction is achieved by applying longitudinal traction and direct posterior-anterior pressure on the humeral head. The arm is then rotated 15 degrees and immobilized in 15 degrees of extension for four to six weeks; this position relaxes the capsule posteriorly and accelerates the healing process [ 9 ]. However, this maneuver could lead to inveterate irreducible dislocations and surgical neck fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction procedures include the McLaughlin operation and its modifications, elevation of the bone defect or anatomic reconstruction with autografts or allografts, humeral rotational osteotomy and posterior glenoid bone blocks [ 7 ]. In case of bilateral PSD, the surgeon should consider the possibility of combining a shoulder replacement in one shoulder with a reconstruction procedure in the other one.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the McLaughlin procedure provides significantly superior results in acute shoulder dislocations, a recent systematic review found that the results were not different in chronic cases 13 . Recently, there have been studies reporting case series of shoulder hemiarthroplasty in cases of chronic posterior shoulder dislocation in which the Hill-Sachs lesions did not even reach 50% of the humeral head.…”
Section: Discussionmentioning
confidence: 99%